2020
DOI: 10.1002/chem.202000659
|View full text |Cite
|
Sign up to set email alerts
|

pH Tuning of Water‐Soluble Arylazopyrazole Photoswitches

Abstract: Arylazopyrazoles are an emerging class of photoswitches with redshifted switching wavelength, high photostationary states, long thermalh alf-lives and facile synthetic access. Understanding pathways for as imple modulation of the thermalh alf-lives,w hile keepingo ther parameters of interest constant,i sa ni mportanta spectf or out-of-equilibrium systems design anda pplications. Here, it is demonstrated that the thermalh alf-life of aw ater-solubleP EG-tethered arylazo-bis(o-methylated)pyrazole (AAP) can be tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 58 publications
1
32
0
4
Order By: Relevance
“…In fact, ITI switches are in this respect on par with other photochromic systems, in which the lifetime of the photochemically produced species can be tuned over several orders of magnitude. 15,21,22,51,52 Importantly, we demonstrated that the protonated ITI 8-H + can be photochemically operated in both directions using low-energy green and red light, similar to the most advanced visible-light-operated P-type photochromes, 21,[53][54][55] albeit the relatively short half-life still remaining a challenge.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, ITI switches are in this respect on par with other photochromic systems, in which the lifetime of the photochemically produced species can be tuned over several orders of magnitude. 15,21,22,51,52 Importantly, we demonstrated that the protonated ITI 8-H + can be photochemically operated in both directions using low-energy green and red light, similar to the most advanced visible-light-operated P-type photochromes, 21,[53][54][55] albeit the relatively short half-life still remaining a challenge.…”
Section: Discussionmentioning
confidence: 88%
“…For a basic characterization of the maximum PSS attainable, we irradiated a solution of iPrO‐AAP‐PEG (1.0 m m in D 2 O) with LEDs of 375 nm and 545 nm (Figure S6,7) until the respective PSS was reached and subsequently recorded 1 H‐NMR spectra (Figure 2 a,b). Once a PSS is reached, iPrO‐AAP‐PEG maintains its E / Z ratio in the time frame of common experiments, because the metastable Z ‐isomer possesses a thermal half‐life of τ 1/2 =5.2 days at 25 °C and pH 7.4 (Figure S8) [28] . A thermal half‐life of more than five days is a very important feature, because we later exploit this deep metastability to not only adjust the PSS , but also to maintain the system at a certain PSS without a considerable decay of the Z ‐isomer.…”
Section: Resultsmentioning
confidence: 99%
“…Für eine grundlegende Charakterisierung des maximal erreichbaren PSS haben wir eine Lösung von iPrO‐AAP‐PEG (1.0 m m in D 2 O) mit 375 nm und 545 nm LEDs bestrahlt (Abbildung S6,7), bis der jeweilige PSS erreicht wurde, und anschließend 1 H‐NMR‐Spektren aufgenommen (Abbildung 2 a,b). Nach Einstellung eines PSS behält iPrO‐AAP‐PEG sein E / Z ‐Verhältnis im Zeitrahmen üblicher Experimente bei, da das metastabile Z ‐Isomer eine thermische Halbwertszeit von τ 1/2 =5.2 Tage bei 25 °C und pH 7.4 besitzt (Abbildung S8) [28] . Eine thermische Halbwertszeit von mehr als fünf Tagen ist ein sehr wichtiges Merkmal, da wir diese tiefe Metastabilität später ausnutzen, um nicht nur den PSS einzustellen, sondern auch um das System bei einem bestimmten PSS zu halten, ohne dass ein nennenswerter Teil des Z ‐Isomers relaxiert.…”
Section: Ergebnisse Und Diskussionunclassified
“…[18] Um ). [28] Eine thermische Halbwertszeit von mehr als fünf Tagen ist ein sehr wichtiges Merkmal, da wir diese tiefe Metastabilitäts p äter ausnutzen, um nicht nur den PSS Vord er rheologischen Charakterisierung der multivalenten Hydrogele haben wir die Überlappungskonzentration c* von sPEG-OH bestimmt (c* = 0.9 mm ;A bbildung S11). [29] AufG rund der Kettenverlängerung wird erwartet, dass die Überlappungskonzentration der sPEG-AAP Die Grundlage der wellenlängengesteuerten Adaption auf Materialebene beruht auf einem multivalenten Ansatz, der abhängig ist von der genauen Kalibrierung des PSS von iPrO-AAP auf molekularer Ebene.Die präzise Kalibrierung zur Einstellung des Verhältnisses von E/Z-iPrO-AAP führt zu einer reversiblen Modulation der mechanischen Eigenschaften der Hydrogele mit einer räumlichen und zeitlichen Kontrolle.J edes intermediäre E/Z-Verhältnis kann mit einem durchstimmbaren Laser erzielt werden, aber auch kostengünstige LEDs decken die gesamte Bandbreite der PSSsa b, wodurch der Ansatz eines präzise einstellbaren PSS füre in breiteres Forschungs-und Anwendungsgebiet geeignet ist.…”
Section: Ergebnisse Und Diskussionunclassified